An LRP1-binding motif in cellular prion protein replicates cell-signaling activities of the full-length protein - Elisabetta Mantuano; Carlotta Zampieri; Pardis Azmoon; Cory B. Gunner; Kyle R. Heye; Steven L. Gonias (JCI Insight, 2023)
Low-density lipoprotein receptor-related protein-1 (LRP1) functions as a receptor for nonpathogenic cellular prion protein (PrPC), which is released from cells by ADAM (a disintegrin and metalloproteinase domain) proteases or in extracellular vesicles. This interaction activates cell signaling and attenuates inflammatory responses. We screened 14-mer PrPC-derived peptides and identified a putative LRP1 recognition motif in the PrPC sequence spanning residues 98–111. A synthetic peptide (P3) corresponding to this region replicated the cell-signaling and biological activities of full-length shed PrPC. P3 blocked LPS-elicited cytokine expression in macrophages and microglia and rescued the heightened sensitivity to LPS in mice in which the PrPC gene (Prnp) had been deleted. P3 activated ERK1/2 and induced neurite outgrowth in PC12 cells. The response to P3 required LRP1 and the NMDA receptor and was blocked by the PrPC-specific antibody, POM2. P3 has Lys residues, which are typically necessary for LRP1 binding. Converting Lys100 and Lys103 into Ala eliminated the activity of P3, suggesting that these residues are essential in the LRP1-binding motif. A P3 derivative in which Lys105 and Lys109 were converted into Ala retained activity. We conclude that the biological activities of shed PrPC, attributed to interaction with LRP1, are retained in synthetic peptides, which may be templates for therapeutics development.